Yemen: Economy-wide impact of conflict and alternative scenarios for recovery - Althibah, Amir M.; Kebsi, Tarek Al; Breisinger, Clemens; Engelke, Wilfried; Tandon, Sharad A.; Raouf, Mariam; Wiebelt, Manfred (International Food Policy Research Institute, 2019)
In addition to the unprecedented humanitarian crisis and the creation of space for militant groups, the conflict in Yemen is also taking a heavy toll on the economy. According to estimates from the International Monetary Fund (IMF 2018), the Yemeni economy may have contracted by about 40 percent between end-2014 and 2018. Sector-specific information on physical damages from the World Bank’s Yemen Dynamic Needs Assessment (World Bank 2018) suggests that damage was worst in the housing sector, where 33 percent of housing units have been either partially damaged or completely destroyed. The education, health, transport, and water, sanitation and hygiene (WASH) sectors have also been severely affected, with overall damage ranging from 27 percent (transport) to 31 percent (WASH). The power and ICT sectors have been somewhat less affected, with estimated damage levels of 13 percent and 11 percent, respectively.